53=600y

Rewrite the equation as 600y=53.

600y=53

Multiply the numerator of the first fraction by the denominator of the second fraction. Set this equal to the product of the denominator of the first fraction and the numerator of the second fraction.

600⋅3=y⋅5

Rewrite the equation as y⋅5=600⋅3.

y⋅5=600⋅3

Multiply 600 by 3.

y⋅5=1800

Divide each term by 5 and simplify.

Divide each term in y⋅5=1800 by 5.

y⋅55=18005

Cancel the common factor of 5.

Cancel the common factor.

y⋅55=18005

Divide y by 1.

y=18005

y=18005

Divide 1800 by 5.

y=360

y=360

y=360

Solve for y 5/3=600/y